Perbedaan Proporsi Sputum Bakteri Tahan Asam Positif pada Pasien Diabetes Melitus Terkendali dan Tidak Terkendali - Harahap, Elga Citra Lylyanti; Purwanti, Angki; Hardianto, Nova (Jurnal Laboratorium Khatulistiwa, 2024)
Currently, when the prevalence of diabetes mellitus (DM) is high and predicted to continue to increase, the elimination of tuberculosis (TB) in Indonesia has not been successful. The challenge is greater due to the comorbidity of both diseases and the complexity of the relationship between the two that is not yet well understood. Therefore, studies on DM-TB comorbidity in various populations are still needed. This study aims to determine the difference in the proportion of positive acid-fast bacillus (AFB) sputum between groups of controlled DM patients (HbA1c <6.5%) and uncontrolled (HbA1c ≥6.5%). The design of this study is cross-sectional, using secondary data (medical records) of 126 DM patients at the Persahabatan Hospital, Jakarta, who underwent examinations in January-June 2024. The results showed that the proportion of positive AFB sputum in the uncontrolled DM patient group was 41.3 percent and in the controlled group was 11.1 percent (based on the Chi-Square test, p-value <0.0001). In addition, the uncontrolled DM patient group had a median (youngest-oldest) age of 55 (37-74) years, while the controlled DM group was 50 (32-70) years (based on the Mann-Whitney test, p-value 0.036). This study shows that the uncontrolled DM patient group had a higher proportion of positive BTA sputum and was significantly older than the controlled DM patient group.